Gender and climate change: regulatory and research advances for climate justice - Mena Gómez, Sileny (2026)
Introduction: This article presents a systematic literature review of regulations and research on climate change that incorporate a gender perspective. Objective: To highlight the main discussions on climate change from a gender perspective at the local and regional levels in Latin America, as well as the regulations related to the need for its inclusion in the study of the climate crisis. Methodology: A systematization of the main legal instruments relevant to the topic was carried out. Research from the last 10 years was also compiled, searching electronic resources subscribed to by the National University of Costa Rica. The review began with the keywords "climate change" and "gender." Subsequently, the documents that support this proposal were selected, prioritizing those that included one of the categories of interest. Results: Costa Rica has robust regulations regarding climate change and gender. However, their implementation faces limitations associated with scarce economic and human resources, political apathy, and low citizen engagement. The research agrees on the urgency of incorporating a gender perspective to achieve climate justice. It shows that climate change impacts are differentiated, with women being the most affected. Conclusions: A gender perspective allows us to identify how climate change differentially impacts people's lives, affecting historically vulnerable populations, including women, to a greater extent.